Land Reform and Changes in Land Ownership Concentration: Evidence from Rice-Growing Villages in the Philippines - Alma M. Dela Cruz; Marife M. Ballesteros (Philippine Institute for Development Studies (PIDS), 2006)
This paper examines the effect of land reform and land transfer actions of farmer beneficiaries on land ownership concentration. A case study of two rice-growing villages was used to track down ownership changes over a period of time. Land reform has succeeded in the break up of huge estates in rice-growing villages but has not effectively improved land ownership concentration due to evasions tactics of landlords who have retained a significant portion of lands to the family through land schemes that are apparently legitimate under the land reform laws. Land transfer actions of farmer beneficiaries have not necessarily worsen the current land ownership concentration but in the absence of progressive land tax, these actions can lead to widening land concentration.
Keywords: 330; land reform; land ownership concentration; land ownership consolidation